Web 2.0: An argument against convergence - Allen, Matthew (First Monday Editorial Group, 2008)
Web 2.0 has been a dominant concept in recent discussion and development of Internet applications, businesses and uses. Dating from 2004, the term Web 2.0 is variously understood as new forms of website development and delivery technology, changing uses of the Internet to emphasise sociability over consumption, new understandings of the possible financial exploitation of the web, and more broadly, a new way of thinking about the Internet as a whole. However, Web 2.0 is, conceptually, both more and less than these various understandings and we can only grasp why it has become such a key term in contemporary usage by appreciating two key discursive foundations for this term. Firstly, much Web 2.0 thinking is a re-expression of long-held ideas about the Internet and the web. Secondly, at the particular time when Web 2.0 was made popular, net technology policy makers and financial analysts were primarily enthused by the possibilities of broadband networks for improved and more profitable versions of the well-established businesses of telephony and audio-visual entertainment, and had to some extent consigned novel, web-based services to a lesser role, following the dot.com crash. Thus, as I argue in this paper, Web 2.0 can be understood as a key intervention, from within the dot.com / new media business sector, recovering from the crash, that re-asserts the equal legitimacy of the use of networked computing, over high-speed lines, for computing-oriented activities, and not just video on demand and voice over IP. In short, in the first years of this century, discussions about the future of the Internet had become dominated by arguments for increased broadband access, substantially concerned with providing more traditional video and voice services in new ways. The World Wide Web was seen as relatively unimportant for this purpose, even though it was part of the so-called 'triple play' of voice and data services. At this time, first in the hands of Tim O'Reilly and then from others who took up his position, Web 2.0 became a catchy simple term under which to mount a campaign for the renaissance of the World Wide Web as a quite distinct, yet equally important, form of media and communications. So, Web 2.0 provides evidence that, while there is a convergence of all forms of media and communications towards similar data traffic over the Internet, there remain diverging views over the nature, control and use of the Internet, views that express the degree to which corporate players imagine themselves to be 'media', 'telephony' or 'computing' in primary orientation.